ADM: una Arquitectura Distribuida Multitarea - Martinez, Alejandro Daniel (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1987: Anais do I Simpósio Brasileiro de Arquitetura de Computadores e Processamento Paralelo, 1987)
Nowdays, the multi-microprocessor architectures are used in computer fields like robotics and artificial intelligence.